Study on Sensing Mechanism of Volatile Organic Compounds Using Pt-Loaded ZnO Nanocrystals - Takeshi Shinkai; Keigo Masumoto; Masaru Iwai; Yusuke Inomata; Tetsuya Kida (Sensors, 2022)
Understanding the surface chemistry of target gases on sensing materials is essential for designing high-performance gas sensors. Here, we report the effect of Pt-loading on the sensing of volatile organic compounds (VOCs) with ZnO gas sensors, demonstrated by diffuse reflection infrared Fourier transform (DRIFT) spectroscopy. Pt-loaded ZnO nanocrystals (NCs) of 13~22 nm are synthesized using the hot soap method. The synthesized powder is deposited on an alumina substrate by screen-printing to form a particulate gas sensing film. The 0.1 wt% Pt-loaded ZnO NC sensor shows the highest sensor response to acetone and ethanol at 350 °C, while the responses to CO and H2 are small and exhibit good selectivity to VOCs. The gas sensing mechanism of ethanol with Pt-ZnO NCs was studied by in situ DRIFT spectroscopy combined with online FT-IR gas analysis. The results show that ethanol reacts with small Pt-loaded ZnO to produce intermediate species such as acetaldehyde, acetate, and carbonate, which generates a high sensor response to ethanol in air.